Exploring differences in student’s Digital Usage Motivations in Kashmiri context - Dar, Wahid Ahmad; Jan, Kounsar (JOURNAL OF INDIAN EDUCATION, 2019)
This study aims at standardising student’s Digital Usage Motivation Scale (DUMS) for identifying various kinds of individual differences among students based on various demographic variables. It aims at understanding influence of gender, residential background and socio-economic status on digital usage motivations. The study is based on a sample of university students of Kashmir. Data was collected through an offline survey (n=704) in compliance with ethical principles of research on human subjects. Using SEM (Structural Equational Modeling), model fit was obtained between hypothesised model and observed data with seven first-order digital usage motives factors as education, capital enhancing, social exchange, self-presentation, self-expression, entertainment and diversion and three second order motive factors as instrumental, socialising and mood management. The study establishes the psychometric properties of DUMS. Study has shown that males and females differ significantly on first order motive factors of education, capital enhancing and self-presentation and second order motive factor socialising. It was evidenced that gender, residential background and socio-economic status significantly influence digital usage motivations. This scale can be useful in understanding individual and group level differences in digital usage motives for successful implementation of ICT in educational settings.